Effect of individual or group culture on in-vitro development of buffalo preantral follicles - Ramesh, H S; Ravindra, J P; Gupta, P.S.P; Kumar, V Girish (The Indian Journal of Animal Sciences, 2007)
A study was made to investigate the effect of individual (single) and group culture on in-vitro development of large preantral follicles in buffaloes. Large preantral follicles of 150 to 500 mm size isolated from slaughterhouse derived ovaries by micro-dissection method. They were placed individually or in groups in minimum essential medium supplemented with steer serum (10%), follicle-stimulating hormone (FSH-0.05 IU/ml), sodium pyruvate (0.23 Mm), glutamine (2 Mm). hypoxanthine (2 Mm), insulin-transferrin-selenium (ITS- 6.25 mg insulin, 6.25 mg transferrin, 6.25 ng sodium selenite), mercaptoethanol (10 mM/ml), gentamicin (50 mg/ml) and cultured in a CO2 incubator up to 100 days. There was no significant difference in the size of follicles between the 2 groups. However, the preantral follicles in-group culture showed a significantly higher growth, growth rate and survivability compared to those individually cultured. Thus culturing of preantral follicles in groups was beneficial for their development during in-vitro condition.